Supramolecular Tandem Assay for Pyridoxal‐5′‐phosphate by the Reporter Pair of Guanidinocalix[5]Arene and Fluorescein - Yu‐Xin Yue; Yong Kong; Fan Yang; Zhe Zheng; Xin‐Yue Hu; Dong‐Sheng Guo (ChemistryOpen, 2019)
Abstract Guanidinocalix[5]arene and fluorescein reporter pair has been chosen to set up a supramolecular tandem assay principle based on the differential recognition of pyridoxal‐5′‐phosphate (the substrate of alkaline phosphatase, ALP), pyridoxal (the product of ALP) and phosphate (the product of ALP). This supramolecular tandem assay system offers an opportunity to monitor the activity of ALP in a label‐free, continuous, and real‐time manner. More importantly, a calibration curve can be given for selective and quantitative detection of pyridoxal‐5′‐phosphate (biomarker for several diseases).